Impact of Acidified Contaminated Soils on Offspring Behavior in Rats - Edariane Menestrino Garcia; Ronan Adler Tavella; Livia da Silva Freitas; Gabriella Mello Gomes Vieira de Azevedo; Gustavo de Oliveira Silveira; Vitoria Machado da Silva; Ana Luíza Muccillo-Baisch; Flavio Manoel Rodrigues da Silva Júnior (Pollutants)
Exposure to contaminated soils can adversely affect health and the well-being of both humans and animals. Environmental stressors can influence the mobility and toxicity of contaminants, altering their potential impacts. This study aimed to assess the impact on the behavior of offspring from rats exposed during the gestation and lactation period to contaminated and acidified soils. Female Wistar rats were gavaged daily for 42 days with soil leachate from an industrial region known to be contaminated with metals and metalloids, using solvents with different pH values (6.0, 5.2, and 3.6). The offspring were evaluated in behavioral tests including Open Field, Elevated Plus Maze, and Inhibitory Avoidance. Our findings revealed significant statistical differences in all three tests conducted, indicating that the exposed groups exhibited lower exploratory behavior, higher anxiety behavior, and lower memory retention than the control groups. The difference was more pronounced in the soil leachate with acidified solvent, at both pH 5.2 and 3.6, suggesting that the combined effect of both stressors led to synergistic interactions, potentiating their impacts. Elemental analysis revealed elevated levels of neurotoxic metals, including Cr, Cu, and Ni, as well as the metalloid As, with acidification significantly enhancing their bioavailability. Moreover, our results demonstrate that acidification facilitated the mobilization of metals and the metalloid As, increasing their bioavailability and acting synergistically to exacerbate the behavioral impacts of contaminated soils. Special attention should be given to populations living in industrial areas that may be exposed to contaminated soils.